To be or not to be faithful: flexible fidelity to foraging trails in the leaf‐cutting ant Acromyrmex lobicornis - Elizalde, Luciana (2012)
1. Ants using trails to forage have to select between two alternative routes at bifurcations, using two, potentially conflicting, sources of information to make their decision: individual experience to return to a previous successful foraging site (i.e. fidelity) and ant traffic. In the field, we investigated which of these two types of information individuals of the leaf-cutting ant Acromyrmex lobicornis Emery use to decide which foraging route to take. 2. We measured the proportion of foraging ants returning to each trail of bifurcations the following day, and for 4–7 consecutive days. We then experimentally increased ant traffic on one trail of the bifurcation by adding additional food sources to examine the effect of increased ant traffic on the decision that ants make. 3. Binomial tests showed that for 62% of the trails, ant fidelity was relatively more important than ant traffic in deciding which bifurcation to follow, suggesting the importance of previous experience. 4. When information conflict was generated by experimentally increasing ant traffic along the trail with less foraging activity, most ants relied on ant traffic to decide. However, in 33% of these bifurcations, ants were still faithful to their trail. Thus, there is some degree of flexibility in the decisions that A. lobicornis make to access food resources. 5. This flexible fidelity results in individual variation in the response of workers to different levels of ant traffic, and allows the colony to simultaneously exploit both established and recently discovered food patches, aiding efficient food gathering.